Disruption based gravitational search algorithm for short term hydrothermal scheduling. Issue 20 (15th November 2015) - Gouthamkumar, N.; Sharma, Veena; Naresh, R.
Highlights: Disruption operator based gravitational search algorithm is proposed. The proposed method is applied to solve short term hydrothermal scheduling. Proper tuning of parameters is done to achieve optimal results. The effectiveness of the proposed approach has been verified on two test systems. Results obtained are validated with other recent reported methods in literature. Abstract: This paper proposes a disruption based gravitational search algorithm (DGSA) to find the optimum solution for short term hydrothermal scheduling (STHTS) problem, which considers the cascading nature of hydro plants, water transportation time delays between reservoirs, variable hourly water discharge limits, reservoir storage volume limits, hydraulic continuity constraint, initial and final reservoir storage volume limits, power system load balance, generation limits of hydro and thermal units and valve point loading effects of thermal plants. In the proposed approach, a disruption operator based on astrophysics has been integrated into gravitational search algorithm (GSA) to enhance its performance. It is found that the disruption operator increases both of the exploration and exploitation abilities in comparison with the conventional GSA. Moreover, an effective strategy is utilized to handle the end storage volume constraints and system load balance constraints. Finally, the proposed approach is evaluated on two hydrothermal test systems, one consisting of four hydro plants and an equivalent thermal plant and another with four hydro and three thermal plants. The comparative result analysis shows that the DGSA approach has better solution results and convergence accuracy than the GSA and other approaches reported in literature for solving STHTS problem.